Implikasi Dan Implementasi Putusan Mahkamah Konstitusi Nomor 91/Puu-Xviii/2020 Terhadap Proses Pembentukan Peraturan Perundang-Undangan Di Indonesia - Saputro, Julianto Dimas; Sinaulan, Ramlani Lina; Suganda, Atma (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Legal certainty is the foundation of a rule of law to clarify legal laws. Despite public debate about Omnibus laws, the Indonesian House of Representatives plenary session adopted the Draft Law on Job Creation in less than a year. The analysis uses descriptive and qualitative methodologies. Descriptive writing analyzes facts by precisely detailing events related to this legislation. This thesis examines the consequences and execution of the Constitutional Court Judgment Number 91/PUU-XVIII/2020 on the Process of Establishing Legislation in Indonesia, so it applies legal theory and concepts to the Court's decision. Constitution. Dogmatic or doctrinal research follows normative legal research. The Court decided that the Job Creation Law violated the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) and had no legal authority if